Teacher's Personality as a Motivation in Arabic Learning: A Systematic Review Based on Five Professional Teacher Personality Frameworks - Adela Anggraini; Sutaman Sutaman; Abdul Muntaqim al Anshory (Universitas Islam Negeri Palangka Raya, 2021)
Studies on the factors that influence students' enthusiasm for learning Arabic are still focused on the strategies and media used. Therefore, this paper presents a systematic study of various educator personalities that can motivate students to learn Arabic. This research used a literature study approach. The articles were selected using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) approach and were analyzed using a framework of five professional teacher personalities. In the results of this study, several essential findings were described: (1) a steady and stable personality is manifested by the conformity of the attitude of Arabic educators to the prevailing norms, (2) mature personality is implemented in a positive enthusiasm of learning interaction between educators and students, (3) an educator's prudent and wise personality in the Arabic learning process is implemented in the form of neutrality or equitable behavior towards all students, (4) an authoritative and polite personality is actualized in a comfortable and positive atmosphere when the Arabic learning process occurs, and (5) a noble character is manifested by the educator